Comparative Transcriptional Signature Analysis of Peripheral Blood Mononuclear Cells in Early Stage of Hepatitis B-related Hepatocellular Carcinoma - Gholizadeh, Omid; Bannazadeh Baghi, Hossein; Ahangar Oskouee, Mahin; Mohammadzadeh, Nader; Naghili, Behrooz; Eslami, Narges; Nasiri-toosi, Mohsen; Hasani, Alka; Ahngarzadeh Rezaei, Mohammad; Taikandi, Tina; Poortahmasebi, Vahdat (Hepatitis monthly, 2022)
Background: Hepatocellular carcinoma (HCC) is a prevalent and life-threatening tumor with high morbidity and mortality. Proper prediction and prognosis are incredibly stressed to diagnose HCC and increase patient survival. Objectives: This research aims to evaluate gene expression levels of pre-differentiated transcripts for those suffering from chronic hepatitis B (CHB) and HCC. Methods: To examine the previously analyzed peripheral blood mononuclear cells (PBMCs) transcriptomic array data, we selected seven differentially expressed genes (DEGs) in normal versus CHB and CHB versus HCC (CD44, SP3, USP8, E2F2, UFM1, IFN regulative factor binding protein 2 (IRF2BP2), and T-cell intracellular antigen 1 (TIA1)). The study included individuals with treatment-naïve CHB (n = 30) and primary HCC (n = 25) and healthy controls (n = 15). Subsequently, the expression of genes was assayed using qRT-PCR. A phylogenetic evaluation was performed using direct sequencing of HBsAg. Results: In HCC patients, 60% (n = 15) were HBeAg-positive. HBeAg was negative in all CHB patients, but all were anti-HBe-positive. The hepatitis B virus (HBV) load of HCC patients was more than that of CHB subjects. All patients were of the Iranian race and HBV D genotype. The expression of five transcriptional markers (CD44, SP3, USP8, E2F2, and UFM1) was higher in HCC patients than in CHB and healthy subjects, which was similar to the initial microarray data analysis. Conclusions: Transcriptional signatures may be related to the pathogenesis of HCC and used as diagnostic biological markers for the initial monitoring and prediction of HCC.